Orientasi Manajemen Pengelolaan Masjid di Ciputat Timur Tangerang Selatan - As’ad; Fatimah; Ananto, Irfan (Presisi Jurnal Pengabdian Masyarakat, 2023)
The activity of social service with the title of "The Orientation of Mosque management in East Ciputat has a purpose of giving a comprehensive understanding about Mosque management to the Mosque keeper. The method that is being used in this activity would be seminar and a training with competent speakers and the Mosque keepers being the audiences of the activity, they are the leader of the Mosque, secretary, and the treasure bill in the area of east Ciputat south Tangerang. This social service activity was being held in Jami At-Taqwa Mosque pondok Ranji East Ciputat